Power Relations and the Tragedy of Love in the 1960 Film The River of Love (Nahr Al-Hub) by Ezzel Dine Zulficar - Shofika Naila Safitri; Rohanda; M Abdul Halim (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
his study aims to reveal: 1) the representation of power relations in the film The River of Love (Nahr Al-hub) by Ezzel Dine Zulficar through the study of Charles Sanders Peirce's semiotics; 2) the representation of the tragedy of love in the film The River of Love (Nahr Al-hub) by Ezzel Dine Zulficar through the study of Charles Sanders Peirce's semiotics. This study uses a qualitative descriptive method with a Peircean semiotic approach that emphasizes the relationship between representament, object, and interpretant. Data were collected using documentation techniques by watching the film and noting relevant scenes and dialogues. The data collection tool used in this study was an observation sheet for recording data compiled based on Charles Sanders Peirce's semiotic framework. The research data were analyzed thematically regarding visual and verbal signs related to the theme of power and love based on time and tool triangulation using the content analysis method within Peirce's semiotic framework. The results of the study show: 1) power relations in this film are represented through male domination over women in the form of social and moral control; 2) the tragedy of love emerges as a consequence of the clash between personal desire and an oppressive social structure. Through the process of semiosis, this film presents love as a space of resistance that ends tragically, while simultaneously criticizing the oppressive social system. Thus, this research contributes to the development of film semiotics and broadens cultural perspectives in modern Arabic literary studies.